Selected papers on Hands-on Science II - Costa, Manuel F. M. (2017)
This second volume of the "Selected Papers on Hands-on Science" the Hands-on Science Network is publishing, reunites some of the most relevant works presented at the 2008, 2009, 2010 and 2011 editions of the annual International Conference on Hands-on Science. From pre-school science education to lifelong science learning and teacher training, in formal non-formal and informal contexts, the large diversified range of works that conforms this book surely renders it an important tool to schools and educators and all involved in science education and on the promotion of scientific literacy.